IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PELAKSANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Awari, Desi; Indriani, Elmiwarti; Marhadi, Hendri; Erlisnawati, Erlisnawati; Mustafa, Nur (STKIP Pesisir Selatan, 2024)
The purpose of this research is to understand the process and challenges in implementing School Based Management (SBM) in the implementation of the Pancasila Student Profile Strengthening Project (P5). The method used is a descriptive qualitative approach with data collection through observation, interviews and documentation. The research subjects were school principals, teachers and students. P5 implementation is carried out through three main stages: planning, implementation and assessment. At the planning stage, the school principal forms a team of profile project facilitators by determining one coordinator, the coordinator guides the project facilitators (all teachers who work at that grade level), identifies school readiness, determines dimensions, time allocation and theme, and designs project modules. In implementation, the teacher begins the activity by introducing the theme, title, objectives and everything related to the project to be implemented. Assessment is carried out by observing student work qualitatively. The research results show that the implementation of School-Based Management contributes to increasing students' understanding of the Pancasila student profile and developing students' character.